COMMUNICATION EFFECTIVENESS ONLINE APPLICATIONS PACU JALUR QUANTAN SINGINGI (IPJKS) AS ONLINE INFORMATION MEDIA FOR COMMUNITY - Disrahayu, Annisa; Rasyid, Anuar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
IPJKS online application is one of the new social media in Indonesia. IPJKS online application is not only effectively used as one of communication tool, but also effectively used as media of information dissemination either general or special information. One of the users who use IPJKS online application is the people who download IPJKS application which this application is used as a medium of information dissemination of tourism on the path of Kuantan Singingi. Theory used is New Media Theory. The purpose of this study is to find out how much the level of effectiveness of onlie tourism applications on the pathway Kuantan Singingi (IPJKS) as an online information media for the community.This study uses quantitative research methods, with data collection techniques that is through the distribution of questionnaires directly to the public who download the online application IPJKS with the number of samples 100 determined by sampling technique. Data analysis techniques in this study using descriptive statistical techniques.The results of this study show that the level of effectiveness of online tourism application communication oacu line Kuantan Singingi (IPJKS) as an online information media for the community is very effective. This is seen from the results of data processing based on six indicators, each indicator reached the scale of 3.43 on the receiver indicator, 3.43 on the indicator of content content, 3.48 scale on the channel indicator (media) , 3.45 scale on the indicator format, 3.47 scale on the source code indicator, and 3.48 scale on the timing indicator, so the conclusion obtained by using the average formula of all indicators is 3, 45 which are included in the effective scale range. This shows that the online application of tourism runway Kuantan Singingi (IPJKS) is a very effective medium as an online informai media for the community.